Ageing in a housing crisis: A gendered lens on housing insecurity and homelessness - Power, Emma; Stone, Wandy; Perugia, Francesca; Veeroja, Piret; James, Amity; Reynolds, Margaret (Council to Homeless Persons, 2023)
Housing insecurity and homelessness are increasing amongst older people in Australia, and women are particularly affected. Our new report, Ageing in a housing crisis: Older people's housing insecurity and homelessness in Australia enumerates the scale of the problem and indicates a structural change in the housing experiences of older people in Australia.1 In this article, a gendered lens draws attention to how women's housing experiences are being adversely shaped and why understanding these experiences matters. We shift attention away from individual factors that drive housing and homelessness risk to focus on systemic challenges and changes within the housing system that underpin increasing life-long gender effects and housing insecurity in Australia.